Over the rainbow: the role of academics in a 'post-hope' South Africa. (2017) - Dodd, Nicole; Merwe, Justin Van Der
The proponents of decolonisation in South Africa's higher education system have tended to overlook the usefulness of critical pragmatism as a guiding paradigm. This article explores the merits of critical pragmatism as a suitable research orientation to resolve the current impasse in South Africa's higher education system. While the arguments for decolonising curricula and academic spaces are valid and credible, promoting decolonisation in a blindly ideological manner, without a sound basis, could be impractical. This article argues that the adoption of critical pragmatism would allow for the achievement of a home-grown, credible research paradigm which encourages researchers to apply a context-specific orientation within developing environments. The article tentatively proposes that blending critical theory with pragmatism would support transformation and development while still maintaining scientific rigour.